2017
DOI: 10.21003/ea.v165-26
|View full text |Cite
|
Sign up to set email alerts
|

Vietnamese small and medium-sized enterprises: legal and economic issues of development at modern stage

Abstract: In Vietnam, developmental ideologies in general and market economic principles in particular have been changed drastically under the transitional system. To build a good platform for small and medium-sized enterprises, Vietnam had to amend some of its most important laws on business. This adjustment was conducted not only in order to improve the existing legislation, but also to facilitate Vietnamese laws to match with the world system, especially taking into consideration the fact that Vietnam is under the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Pham and Talavera, 2018). Given that existing policies are not yet protective of the rights and needs of firms (Hoa and Khoi, 2017;Thai and Ho, 2010), more attention should be given to better allocate national resources among state and non-state sectors to eradicate any discrimination and promote efficiency and productivity of both sectors (Nguyen and Mort, 2016;Thi Nhung, Gan and Hu, 2015). Specific suggestions include reducing tax and improving loan access (Hoa and Khoi, 2017), decentralizing policy-making to better support SMEs (Cox and Le, 2014;Le et al, 2016;Paswan and Tran, 2012;Tran and Santarelli, 2017), and increasing trust in the government at the community level (Dut, 2015;Nguyen and Wongsurawat, 2012;Phuong, 2014).…”
Section: Strong Focus On Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Pham and Talavera, 2018). Given that existing policies are not yet protective of the rights and needs of firms (Hoa and Khoi, 2017;Thai and Ho, 2010), more attention should be given to better allocate national resources among state and non-state sectors to eradicate any discrimination and promote efficiency and productivity of both sectors (Nguyen and Mort, 2016;Thi Nhung, Gan and Hu, 2015). Specific suggestions include reducing tax and improving loan access (Hoa and Khoi, 2017), decentralizing policy-making to better support SMEs (Cox and Le, 2014;Le et al, 2016;Paswan and Tran, 2012;Tran and Santarelli, 2017), and increasing trust in the government at the community level (Dut, 2015;Nguyen and Wongsurawat, 2012;Phuong, 2014).…”
Section: Strong Focus On Managementmentioning
confidence: 99%
“…Given that existing policies are not yet protective of the rights and needs of firms (Hoa and Khoi, 2017;Thai and Ho, 2010), more attention should be given to better allocate national resources among state and non-state sectors to eradicate any discrimination and promote efficiency and productivity of both sectors (Nguyen and Mort, 2016;Thi Nhung, Gan and Hu, 2015). Specific suggestions include reducing tax and improving loan access (Hoa and Khoi, 2017), decentralizing policy-making to better support SMEs (Cox and Le, 2014;Le et al, 2016;Paswan and Tran, 2012;Tran and Santarelli, 2017), and increasing trust in the government at the community level (Dut, 2015;Nguyen and Wongsurawat, 2012;Phuong, 2014). (Dang et al, 2016;Nguyen and Nordman, 2018;Nguyen and Mort, 2016;Perri and Chu, 2012;Vuong, 2016a;Vuong and Napier, 2015) 2 Resources management 53 (Chu and Luke, 2012;Duy and Oanh, 2015;Nguyen et al, 2015;O'Cass et al, 2012;Pham and Talavera, 2018;Turkina & Thi Thanh Thai, 2013;Thai and Ho, 2010;Vuong, Do and Vuong, 2016a) 3 Business efficiency 38 (Hiep and Van Vu, 2015;Hoa and Khoi, 2017;Lensink and Pham, 2012;Nguyen et al, 2013;Santarelli and Tran, 2013;Tran and Santarelli, 2017;Walder and Nguyen, 2008) 4 Innovation and creativity 38 (Brundenius and Le, 2014;Kiura et al, 2014;Le et al, 2018a;…”
Section: Strong Focus On Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have also pointed out that developed policies have not been implemented properly to protect the rights and needs of firms (Hoa and Khoi, 2017;Thai and Ho, 2010). Contradict to previous findings that bribery or 'speed money' can help firms reduce cost arising from the complex and unpredictable legal practices in a transitional context, several studies on corruption have revealed that corruption has had a negative impact on firms' productivity and their abiding by state regulations (Tran et al, 2016;Vu and Le, 2016;Vu et al, 2018).…”
Section: Law Regulation and Policymentioning
confidence: 99%
“…New regulations on property rights and land ownership which are more open to entrepreneurs of various nationalities are also highly appreciated for the rise of SMEs in Vietnam. It has also been reported that despite the reported ineffectiveness of fiscal fund aid, other financial policies such as tax reduction, loans support and are still considered to have successfully eliminated financial burdens faced by startups in the period of crisis (Hoa and Khoi, 2017).…”
Section: Law Regulation and Policymentioning
confidence: 99%